التحلیل اللاحق للانتاج الفکرى الصادر فى مجال التصنیفات العالمیة للجامعات وتأثیره على النشر الدولى - د. أسماء سید محمد حسنین Mohamed Hassanein (المجلة الدولية لعلوم المكتبات والمعلومات)
Meta- analysis is considered as a method of research in the field ofMeta- analysis is considered as a method of research in the field of libraries andinformation and one of the efforts of documentation of intellectual production.This method is characterized by three characteristics that do not exist withoutthem: Integration (consolidation or integration) between the results of previousstudies, Summarizing, comparing and comparing these results, Use some statistical methods in this summary to perform bibliometricanalyzes of previous studies,And this study aims to apply the method of Meta-analysis of the one oftopics of libraries and information is "the World University Rankings and its effecton Scientific Publishing"